Analisis Path: Peran Live Streaming, Citra Merek, dan Kualitas terhadap Keputusan Pembelian Shopee dengan Mediasi Voucher - Tarigan, Arihta; Noor, Laili Savitri; Maharani, Keythline Priscilla Putri (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2024)
Research aims: This study aims to determine the role of brand image, product quality, and live streaming in buying decisions on Shopee to profound marketing strategy optimization, implementing voucher promotion strategies, developing live services, and understanding consumer trends in the e-commerce industry with discount voucher as the intervening variable. Methods: This research used quantitative associative methods with data collection based on online questionnaires and analyzing data through path analysis. Research Finding: Based on the results of this study, it can be concluded that brand image and live streaming have a significant effect on discount vouchers, which in turn influence purchase decisions, with a significant indirect impact primarily through live streaming.. Theoretical contribution/Originality: This study enriches the literature by confirming that these factors significantly influence purchasing decisions, particularly on e-commerce platforms like Shopee, and highlights the importance of social media and digital promotions in influencing consumer behaviour. Practitioner/Policy implication: An e-commerce company should prioritize marketing strategies that involve a strong brand image, guaranteed product quality, and live streaming as an interactive medium to attract consumer interest. Research limitation: The research results cannot be generalised to the entire population because data collection uses the SEM (Structural Equation Modeling) method with limited respondents.